Exercise 1.2
Exercise 1.2
Exercise 1.2
11111
Solution
We have a + b + c = 25 . .. (1)
2, a, bare in A.P.
⇒ 2a = 2 + b . . . (2)
Also b, c, 18 are in G.P
⇒ 18b=c . . . (3)
2
02 1111
Solution
~s. 2, 5, 8, ..
:,ol. (a+ 2d ) = 4a
⇒ 3a = 2d
We have given that a+ 5d = 17
a=2 , d=3
so series 2 , 5 , 8 .... .. .
03 1111
Solution
2
"he given sum S = (x + y) +(x + xy
-y2)+ ....
~
2
X y ( 1~ X 1~\ )
2
1 ( x - y2 - xy2 + xy2 ) -
x- y l (1 - x)(1-y) -
x + y - xy
.. ,
04
Solu tion
Ans. 612
Sol. a+2 d=1 8
a+ 6d = 30 ⇒ 4d = 12
⇒ d=3 & a=1 2
1
S,, = ; [2(12 )+ 16(3)]
17
= [24+ 48] =17 x 36= 612
2
05
~ Report t he questio n
Solu tion
an - 1 · a2 > a1 · an
an . a1 = a1 . an
multiplying we get
a12 . a2,
2 -- ..
.. .an2 > ( a 1 . an )n .
06
Solu tion
~s . 11
Sol. a =- 9 , d = 3
n
66 = [-1 8 + (n- 1) 3]
2
n
66 = [-1 8 + 3n - 3]
2
132 = 3n2 -21 n
n = 11
07
Solution
n
[a1 + ((k - 1)n + 1- 1)d + a1 + (kn - 1)d]
2
08 1111
Solution
Ans. 128, 771
Sol. (i)994=105+ (n-1)7
⇒ 889 + 7 = 7n ⇒ n = 128
09 1111
Solution
_et 8 be them th. 12 then th and 27 be the t th
terms of a G.P. whose first term is A and
:ommon ratio is R.
1
rhen 8 = ARm . '. 12 =AR" · ', 27 = AR • 1
2
⇒ !_=
12
Rm-n = 2 13' !3.
27
=Rn-t =(±)
3 '
~ =Rm-t =(~r
:::;, 2m - 2n = n - t and 3m - 3n = m - t
Solution
Ans. 19668
Sol. First No. = 103
last No. = 791 No. of terms = 44
44
s= (103+791)
2
= 22 (894) = 19668
11 1111
n
Let S=I,a; and show that
i- 1
n s n2
I , - - > - - assuming not
i- t s - a; n- 1
all a s are equal.
1 '
Solution
AM 1 =~
n
±- 5
-
_ S - 81
11
, GM,
{u ~ f'" 5 81
(TI denotes product
sign)
And AM 1 > GM 1 (as a 's are not 1
-}(f_s
n l 1-,
)(f~J>
l 1-, s - a; s
1
n 5 n2
⇒ Ls-a-> (n-1)
1- 1 I
12 1111
p'" term is f + 2.
Solution
Ans. 160
Sol. Given that
T =
p
£.7 +2
'
1 p(p + 1)
then s, = 7 :Ep + :E2 = - -
14
+ 2p.
taking p = 35
s,. = 160
13 1111
Solution
Let first term = a Common difference = d,
S,,, = sum of first m terms.
Then given Sm= Sm +n - Sm= Sm +p -Sm
Sm= Sm +n -5m ⇒ 2Sm = Sm +n
⇒2 m ( 2a +(m - 1) d) = -m +-n [ 2a +(m + n - 1)d ]
2 2
2a [2m- m-n] = d [m 2 + n2 + 2mn-m-n-2m2 + 2m]
2 2
2a [m - n] = d [ n - m + 2mn + m - n] .... (1)
also 28,,,=S,,, .,
⇒ 2a [m-p] = d [p2 - m2 + 2mp + m-p] .... (2)
from (1) and (2)
⇒ n2 - m2 + 2mn + m - n p2 - m2 + 2mp + m - p
m- n m- p
⇒ (m + nl(~ - ¾l = (m + p)(~ - n
14 1111
Solution
Ans. 4 , 9, 14
Sol. Numbers are a - d, a. a + d
s = a - d + a + a + d = 27
⇒ a=9
a(a 2 -c:l2) = 504
9(81-d 2 ) = 504
81 - d2 = 56
d2 = 25 ⇒ d =± 5
Numbers are 4 , 9, 14
15 1111
Solution
(s - a2 ) + (s - a3 ) + ..... + (s - an ) >
n- 1
((s - a2 )( s - a3 ) ....... (s - an ))" "_,
~
1
2' [( s - 81 )( s - a2 )( s - 84 ) . . . . (s - an )]" "-
n- 1
Solution
Sol. (i) a, b, e are in A.P.
a (ab+ be+ ae). b(ab +be+ ae), e(ab
+be+ ae) are in A.P.
⇒ a2 (b + e), b2 (e + a), e2 (a + b) are in
A.P.
(ii) b + e - a, a+ e - b, a+b
-e are inA.P
⇒ 2(a + e-b) = (b + e - a) (a + b - e)
⇒ a+e=2b
⇒ a . b . e are in A.P
17 1111
Solution
Consider the positive numbers
a' . a' ..... ky times and bY, b'. .... kx
times
For all these numbers,
AM
(a' + a' + ....ky times) + (b' + b' + .. .kx times)
kx + ky
kya' + kxaY
k (x + Y)
GM=
1
/( a' .a' ....ky times) (bY .bY .. .. kx times ))•(•-Y I
1
= ( a•lky). bY("' I )•1•-YI
k,y ,y
=(ab}•(•-Y I = (ab}(,-y)
.... (1)
As .! + .!=1 . ~=1,i.e. x+ y=
X y xy
xy
.-. (1) becomes ya• + xaY ~ ab or
xy
a• aY
- + - ~ ab .
X y
18 1111
Solution
Ans. 128
Sol . Let the three terms be a. ar. ar 2
ar2 = a2 :::::;:. a = r2 and ar
8
⇒ r3 = 8, r = 2 and a=4
r. =4(2) 5 = 128
19 1111
f(x) = x - 2x + 3x 2 3
- .... + (-1),._ 1
n.x" where xe R then find f'(1/2).
Solution
Here f'(x) = 1 - 22x + 32x2 - 42x3+
... .+ (-1 ),.__, n2xn---1
2 2 2
. t·( i ) = 1- 2 .i + 3 Hr + 4 ( i r +
..... + (-1)n-1 n2 G r
22 32
· - it H )=-f i + (i r - G r +
20 1111
Solution
Ans. 2, 6, 18
1 156
⇒ (1+r+ ,=-) =
36
1 13
1+r+ - = -
r 3
r=3 or1/3
Numbers are 2, 6, 18
21 1111
If the p~ , q~ , rt"
terms of a G.P. be a, b, c
respectively, prove that a•~ b'-<> c•-<t = 1.
Solution
Sol. Tp =AR• -• =a
T, =AR0 - 1 =b
T, =AR'-' =c
So a0 -r. b' -•. c• - 0 = AD. RD= 1
22 1111
Solution
Ans. 6, -3 , 3/2, ····· ·
Sol. a = 4
1-r
a3
1-r3 = 192
(1 - r)3 192
⇒ ~ = (4)3
⇒ (1-r)2 = 3
1 + r +r 2
⇒ 1 + r2 - 2r = 3 + 3r + 3r2
⇒ 2r2 + Sr + 2= 0
⇒ (2r + 1) (r + 2) = 0
r = -1/2, r = -2(rejected)
When r = -1/2 , a= 6
so series is 6, -3, 3/2 .....
23 1111
(ii) are i n
a 2 + b2 ' b2 + c2 ' cz + dz
G.P.
Solution
Sol . (i) Let b = ar
c = ar2 and
d = ar'
So a' (1- r' ),a' (r2 )( 1 - r' ),a' r'(1 -r2 ) these
are in G.P.
So (a' - b' ), (b' - c'), (c' - d') are in G.P.
1 1 1
(ii) a 2 + b2 ' b2 + c 2 ' c 2 + d2
1 1 1
= a2 (1 +r 2 ) • a2 r 2 (1+r 2 ) • a2 r 4 (1+ r 2 ) are in
G.P.
24 1111
Solution
1
Ans.
11
1
Sol. T1 = 20 ⇒ a+ 6d = 20
1
T13 = 38 ⇒ a+ 12d = 38
d = 3, a= 2
1
so
11
25 Ill
Sum the following series
2 3 4
(i) 1+ + + + ..... to n terms.
2 22 23
3 7 15 31
(ii) 1+ 4 + 16 + 64 + 256 + ····· to
infinity.
Solution
8
Ans. (i) (ii)
3
n
T. = 2n- 1
2 3 n
s = 1+ 2 + ~+ ............+ 2n-1
... (i)
1 1 2 (n -1) n
2s = 2 + 22 + ......... + -2-n--1- + -
2"
...(ii)
(i)-(ii) we get
1 1 1 1 n
2S= [1+ 2 + ~+ ........ + 2"_, J-2"
n
2"
(ii) S = 1 + 3 + !_ + 15 + - 31 +
4 16 64 256
•• <f> ••••• (i)
1 1 3 7
45 = 4 + w + 64 + · ······"'
.. (ii)
(i)- (ii), we get
3 1 1
45 =1+ 2 + 4 + a1 + ······· ·<$)
3 1 8
45 =m ⇒ s=3
26 Ill
Find the sum of n terms of the series the rt"
term of which is (2r + 1 )2'.
Solution
Ans. n.2° · 2 - 2• · 1 +2.
Sol. T,= (2r + 1) 2'
S = 3.2 + 5.22 + 7.23 + .........+ (2n + 1) 2"
...(i)
2S = 3.22 + 5.23 + .........+ (2n + 1) 2" + (2n + 1)
2"-1 • ••(ii)
(i)-(ii)weget
-S = 3.2 + (2.22 + 2.23 + ..... + 2.2")-(2n +1)
2"·'
-S = 6 + 8 (2~' - 1)-(2n + 1) 2" 0
'
Solution
Ans. a= 4, b = 8
a+b =
Sol. 6
2
G2 + 3H = 48
2ab
⇒ ab+3 - - =48
a+b
3ab
⇒ ab+ =48
6
3
⇒
2 ab=48
⇒ ab= 32
a =4 8
'
28 1111
Solution
Sol. Let the numbers are a. b
2a + b a +2b
A,= - 3- , A2 = - 3-
2a+ b
H2 = 3ab
G1 G2 A1 + A 2
Now ~ = ~⇒
1 2 1 2
1 1 1 a+b
L.H.S. = H, + H2 = 3ab 3(a + b) = °a"b
3(a + b)/ 3 a +b
R.H.S. = ab = °a"b ⇒ L.H.S. =
R.H.S.
29 1111
Solution
rr
Sol. (i) O< 8 <
2
tan8 , cot8 > 0
AM ;, GM
tana + cota )
( - -2- - :e (tana .cota)•n
(tan a + cota) :e 2
(ii) (x'y + y2z + z2x) (xy2 + yz 2 + zx 2 ) :e
9x 2y2 2 z
x2y + y 2z + z2x
:e (x'y . y2z . z 2x)'"
3
x 2y + y2z + z 2x :e 3xyz
..... .(i )
30 1111
Solution
Ans. (i ) 2°• 2 - 3n-4
S,= IT,
= I (2""'-3)
= (2""'-4) -3n
= 2""'-3n-4
(ii) S = 3 + 33 + 333 + 3333 + ........ n
term .
3
S=
9 [9 + 99 + 999 + ......... n term]
_ _:3_ [1 0(10" - 1) - n] 3
- 9 10 - 1 [10"' 1 - 9n -
81
10]
31
Solution
An l- (1)
,
\2 -
,
4(211 11(2n , l ) (iJ
"
10
ln •1 J(n • 2J !n•3)(2n •l)
Sol. {t) ,
S • U. S. . 3.5.7 • $79 ' '
T ,.
-( r - l ) r (r • l }lr • 2 ){r • 3 )
' ,
• S 11 .2-J.4.5- 0J • s l2. 3., .5.6-1-2.3.4.SJ
• ~ [3 • .5 .6 7 - 2.3.4 5 .GJ •
1
• 5 (n(n • 1) /n • 2J(n • J)
8 1 • ¾ ln (n• 1/tfl • l )
\ n•l )(n•4)J
,
• , tJ..4.5.6 -2 .3.4.!!IJ
. • : [n(n • l )Cn • 2 )
S, =~ [n (n • 1) (n • 2)\n • lJI
32 1111
Solution
Ans. 3 . 7. 11 or 12 . 7. 2
Sol. let a- d , a, a +d
3a = 21
:::::, a=7
a -d. a-1. a +d+ 1are inGP
7 - d. 6 , B+d are inG.P
36 = (7- d)(B+d)
36 =56- d -d'
:::::, cf + d- 20 = O
:::::, d= -5 . 4
so Numbers are 3. 7. 11
12 . 7. 2
33 1111
Solution
Ans. -9..:!:.
p- q
Tq Tr
Sol. ,:;;- = Tq =common ratio
a + (q - 1)d = a + (r - 1)d
a +(p- 1)d a + (q- 1)d
using dividendo
__B::!)}_ = ___ir__::_9)_
a + (p- 1)d a +(q- 1)d
34
Solution
1
(i) n (n + 1) (2n + 7)
6
1
(ii) - (3n+1 + 1) - 2n+1
2
Sol. (i) Tn = n(n + 2)
Sn = L Tn = L n2 + 2n
n(n + 1)(2n + 1) 2n(n + 1)
- +---
6 2
= n(n2+ 1) [2n3+ 1 + 2]
s. = ~ (3n+1 + 1) - 2°• 1